(untitled) (Bangladesh Journal of Plant Taxonomy, 2018)
This study was carried out to provide the baseline data on the composition and distribution of the angiosperms and to assess their current status in Rajkandi Reserve Forest of Moulvibazar, Bangladesh. The study reports a total of 549 angiosperm species belonging to 123 families, 98 (79.67%) of which consisting of 418 species under 316 genera belong to Magnoliopsida (dicotyledons), and the remaining 25 (20.33%) comprising 132 species of 96 genera to Liliopsida (monocotyledons). Rubiaceae with 30 species is recognized as the largest family in Magnoliopsida followed by Euphorbiaceae with 24 and Fabaceae with 22 species; whereas, in Lilliopsida Poaceae with 32 species is found to be the largest family followed by Cyperaceae and Araceae with 17 and 15 species, respectively. Ficus is found to be the largest genus with 12 species followed by Ipomoea, Cyperus and Dioscorea with five species each. Rajkandi Reserve Forest is dominated by the herbs (284 species) followed by trees (130 species), shrubs (125 species), and lianas (10 species). Woodlands are found to be the most common habitat of angiosperms. A total of 387 species growing in this area are found to be economically useful. 25 species listed in Red Data Book of Bangladesh under different threatened categories are found under Lower Risk (LR) category in this study area.